SEXUAL ABSTINENCE AND IMMOBILISATION STRESS DECREASED NITRATE + NITRITE CONCENTRATION AND INCREASED NECROTIC OF PENILE CORPUS CAVERNOSUM SMOOTH MUSCLE AND ENDOTHELIAL CELLS OF ADULT MALE MICE - Karmaya, I.N. Mangku; I. Pangkahila, Wimpie; Pangkahila, J. Alex (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Sexual intercourse in adult people is not only related to reproduction,recreation and better relation but also for maintaining good health. Regular andfrequent sexual intercourse has protective role for cardiovascular disease, malignancyand often related with longevity. On the contrary less frequent sexual intercourse isoften correlated to early death and reproductive organ disorders. One main factorwhich involve in any process related to sexual intercourse is nitric oxide. Thisresearch aims to know the declination of total nitrate and nitrite concentration as themain oxidation product of nitric oxide and necrosis of the endothelial and smoothmuscles of corpus cavernosum after three month sexual intercourse abstinence andstress immobilization.By randomized pretest-posttest control group design, the research wasconducted in adult male mice (Mus musculus) which were divided into four groups.each consisted of seven mice. One group as a control and the other three wereexposed to sexual abstinence, immobilization stress and the combination of sexualabstinence and immobilization stress in three months period. The investigation wascarried out to the penile total nitrate and nitrite concentration and the histologicalchanges of the middle part of the penile shaft. To know the degree of lesion then thecalculation of the histologic features was done in five view fields of every preparat.The result was compared to control group.In this research, the mean of total nitrate and nitrite decline and the lowest wasfound in the combine intervention groups with significance level p < 0,005. Thecorpus cavernosum in the intervention groups showed multifocal necrosis onendothelial and smooth muscle cells of corpus cavernosum with picnotic nuclei,irregular form and dark colour. Some muscle cells are lysis. These features werefound in three among seven samples in sexual abstinence group, two among sevensamples in immobilization stress group and in all samples of combined interventiongroup.Conclusions can be drawn from this research are that the sexual abstinence,immobilization stress and the combine interventions decline the nitrate and nitriteconcentrations and induce endothelial and smooth muscle cells necrosis of the copuscavernosum.
Keywords: sexual intercourse abstinence, stress immobilization, total nitrate nitrite and necrosis.